2015
DOI: 10.1021/acs.iecr.5b00460
|View full text |Cite
|
Sign up to set email alerts
|

Water Treatment Capacity of Forward-Osmosis Systems Utilizing Power-Plant Waste Heat

Abstract: Forward osmosis (FO) has the potential to improve the energy efficiency of membrane-based water treatment by leveraging waste heat from steam electric power generation as the primary driving force for separation. In this study, we develop a comprehensive FO process model, consisting of membrane separation, heat recovery, and draw-solute regeneration (DSR) models. We quantitatively characterize three alternative processes for DSR: distillation, steam stripping, and air stripping. We then construct a mathematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 26 publications
(70 reference statements)
2
32
0
Order By: Relevance
“…It should be noted that an energy consumption rate of 0.73 kWh m -3 would be expected for draw solute regeneration (0.50 ± 0.01 mol L -1 initial diluted draw concentration, low-pressure single distillation column) (McGinnis and Elimelech 2007). Recent research confirmed that this part of energy consumption could be compensated by waste heat, and hence it was not counted in the evaluation in this study (Zhou et al 2015).…”
Section: Energy Consumptionmentioning
confidence: 94%
“…It should be noted that an energy consumption rate of 0.73 kWh m -3 would be expected for draw solute regeneration (0.50 ± 0.01 mol L -1 initial diluted draw concentration, low-pressure single distillation column) (McGinnis and Elimelech 2007). Recent research confirmed that this part of energy consumption could be compensated by waste heat, and hence it was not counted in the evaluation in this study (Zhou et al 2015).…”
Section: Energy Consumptionmentioning
confidence: 94%
“…However, the vapour pressure of the thermoresponsive DS considerably exceeds that of water, which is desirable as the draw solute can be easily vaporised in a distillation process operating at relatively low temperatures (McCutcheon et al 2005). Although the draw solute decomposes at low temperatures (60˝C at 1 atm (McGinnis & Elimelech 2007)), the distillation column still has to be operated at significantly higher temperatures to completely remove any ammonia trace (ă 1 ppm) from the brine and product stream (Zhou et al 2015).…”
Section: Low Viscositymentioning
confidence: 99%
“…Non-toxic: Toxic solutes in the brine stream or in the final freshwater product can have detrimental effects. Ammonia is toxic above a certain threshold, hence the final water quality needs to present less than 1 ppm of ammonia (including related species such as ammonium and carbamate) in the permeate and brine stream to adhere to the limits specified in the Guidelines for Drinking Water Quality (WHO) (Zhou et al 2015, Chekli et al 2016).…”
Section: Low Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…The scarcity of drinking water in some locations has motivated the search for new and efficient water desalination solutions. The Forward Osmosis (FO) process has gained considerable interest in recent decades because of its capability of using low‐grade energy [ 1–3 ] from renewable sources [ 4–7 ] to operate. FO is a membrane separation process in which the mass transfer of water across the membrane is driven by the osmotic pressure gradient between a draw solution (DS) and a feed solution (FS).…”
Section: Introductionmentioning
confidence: 99%